2020
DOI: 10.1055/a-1089-7870
|View full text |Cite
|
Sign up to set email alerts
|

Updates on the Management of Thyroid Cancer

Abstract: The diagnostic modalities, stratification tools, and treatment options for patients with thyroid cancer have rapidly evolved since the development of the American Thyroid Association (ATA) guidelines in 2015. This review compiles newer concepts in diagnosis, stratification tools and treatment options for patients with differentiated thyroid cancer (DTC), medullary thyroid carcinoma (MTC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
108
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(113 citation statements)
references
References 110 publications
0
108
0
5
Order By: Relevance
“…Some studies reported that age ≥70 years old was an indicator of poor survival for ATC patients (Onoda et al, 2020;Sugitani et al, 2012). Some studies reported that people younger than 60 years old had superior prognosis (Araque, Gubbi & Klubo-Gwiezdzinska, 2020;Roche et al, 2018). Taken these into consideration, we divided patients into <65 and ≥65 years old groups.…”
Section: Covariatesmentioning
confidence: 99%
“…Some studies reported that age ≥70 years old was an indicator of poor survival for ATC patients (Onoda et al, 2020;Sugitani et al, 2012). Some studies reported that people younger than 60 years old had superior prognosis (Araque, Gubbi & Klubo-Gwiezdzinska, 2020;Roche et al, 2018). Taken these into consideration, we divided patients into <65 and ≥65 years old groups.…”
Section: Covariatesmentioning
confidence: 99%
“…In this subgroup of DTC patients, the 10-year survival rate is less than 20% [2]. In medullary thyroid carcinomas (MTCs) distant metastases are present at diagnosis in 7-23% of patients and represent the main cause of cancer-related death with a 10-year survival rate disease ≤40% compared to a 10-year overall survival of 75% observed in unselected MTC patients [3,4]. Four multikinase inhibitors (vandetanib, cabozantinib, sorafenib and lenvatinib), all targeting the vascular endothelial growth factor receptor (VEGFR), have obtained regulatory approval for advanced thyroid cancer as a result of significant improvement in progression free survival (PFS) demonstrated in phase III trials [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the NCCN guidelines for MTC management suggest that pembrolizumab should be considered in patients with symptomatic, progressive MTC with high TMB (≥10 mutations/megabase) [ 6 ]. Pembrolizumab (NCT03072160, NCT-02721732), nivolumab (NCT03246958), and ipilimumab (NCT-03246958) are currently being evaluated in phase 2 trials for the treatment of recurrent or metastatic MTC [ 41 ].…”
Section: Management In Persistent or Recurrent Mtcmentioning
confidence: 99%